Respons Khalayak terhadap Vandyke Brown Print - Irwandi And Edial Rusli (Rekam: Jurnal Fotografi, Televisi, Animasi)
This article discusses the forms of old print socialization to the community through the implementation of promotional mix method. The efforts were made to encourage the demand for old print products effectively to potential target audiences as well as looking for markets that form the foundation needs to be prepared. Print method that socialized is vandyke brown print. This method, based on the SWOT analysis is potentially the largest to be marketed to the public. The activites of promotional mix in this research are socialization, recruitment, workshop for potential stakeholders, such as photography business, Student Activity Unit, photography community, and high school students / vocational and promotion in various media. The result of socialization through the promotional mix shows that the target audience wants utilize old photographic print in their activities. They want to be able to do their own old printing process the print, the constraint is plagued with expensive materials. It cannot be purchased in retail. Audience response in this study should be followed by opening a new market space for the old print in Indonesia. One of the the new market here is old print service print services print and sales of chemical and materials to print with the old method of print.